Nickel-cobalt-lithium selective adsorbent, method for preparing same, and use thereof
Patent Information
- Application Number
- CN202510557790.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-29
- Publication Date
- 2026-10-30
AI Technical Summary
[0003]目前用于固相萃取的树脂,尤其是负载有机官能团的树脂,大多数没有很高的选择性,无法达到选择性吸附、纯化的目的
[0012]本发明的镍钴锂选择性吸附剂对镍、钴、锂的选择性高,制备简单,使用其进行分离纯化时效果好,绿色环保,成本低。
Smart Images

Figure CN122999153A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of organic synthesis technology, specifically to a nickel-cobalt-lithium selective adsorbent, its preparation method, and its application. Background Technology
[0002] Compared with traditional methods, resin solid phase extraction has advantages such as no emulsification, low loss, simple operation, low pollution, low cost, and multiple cycles.
[0003] Currently, most resins used for solid-phase extraction, especially those loaded with organic functional groups, do not have high selectivity and cannot achieve selective adsorption and purification.
[0004] Therefore, it is necessary to develop new adsorbents to further improve the selectivity of solid-phase extraction processes, thereby enhancing the separation and purification of certain metal elements (especially nickel, cobalt, and lithium). Summary of the Invention
[0005] One object of the present invention is to provide a new adsorbent that has high selectivity for nickel and cobalt, and can separate nickel and cobalt from calcium and magnesium; it also has high selectivity for lithium, and can be used for the separation and extraction of lithium from solutions containing lithium ions and sodium ions.
[0006] Therefore, according to a first aspect, the present invention provides a nickel-cobalt-lithium selective adsorbent, characterized in that it has the structure shown in Formula I: (Equation I) in: M is the resin matrix; A is selected from -O- and -NH-(CH2). t - and -NH(CH2) n NH-, where n is an integer from 2 to 9, and t is an integer from 0 to 9; B is either C or S=O; X is C, CH, or N; D, together with B and X, can form a saturated or unsaturated ring structure containing one or two heteroatoms, or a benzo[a] ring structure. The ring structure or benzo[a] ring structure is optionally composed of one or more elements selected from C1-C2. 20 Alkyl, C1-C 20 Alkoxy, C6-C 12 Aryl, optional C1-C 20 The groups that replace amino, hydroxyl, fluorine and chlorine atoms are selected from N, O and S heteroatoms, and the ring structure is a 5, 6 or 7-membered ring structure.
[0007] According to a second aspect, the present invention provides a method for preparing the above-mentioned nickel-cobalt-lithium selective adsorbent, characterized in that it includes one of the following steps S1, S2, S3, S4, and S5: S1. A resin containing primary amine groups is reacted with a compound of Formula II in the presence of a catalyst at a temperature of 40-120°C via an amine-ester exchange reaction to obtain the nickel-cobalt-lithium selective adsorbent. (Formula II) in: Y is C1-C 10 alkoxy groups; D, B, and X are as defined with respect to equation I. S2. In an acidic solution in the presence of aldehydes, a resin containing primary amine groups is reacted with a ketone of Formula III at a temperature of 40-120°C to obtain the nickel-cobalt-lithium selective adsorbent. (Formula III) in: D, B, and X are as defined with respect to equation I. S3. H2N-(CH2)n-NH2 is subjected to an amine-ester exchange reaction with the compound of formula II to obtain the intermediate of formula IV. Then, a substitution reaction is carried out between the intermediate of formula IV and the chlorinated polyol resin to obtain the nickel-cobalt-lithium selective adsorbent. (Formula IV) in: n is defined for equation I. D, B, and X are as defined with respect to equation I. S4. Add alkaline solution to the reaction vessel containing the swollen chlorine bead resin, heat to induce a hydrolysis reaction, separate the resin after the reaction, wash repeatedly with solvent to obtain the hydrolyzed chlorine beads, place the hydrolyzed chlorine bead resin in a reaction vessel, add a solvent to swell the chlorine bead resin, a compound of formula II, an acid-binding agent, and a co-catalyst, heat under reflux to induce a substitution reaction, and obtain the nickel-cobalt-lithium selective adsorbent, wherein the compound of formula II is as defined in step S1. S5. A substitution reaction is carried out between the resin containing primary amine groups and the compound of formula V in an alkaline solution under heating conditions to obtain the nickel-cobalt-lithium selective adsorbent. in: (Form V) in: Y is either Cl or Br; q is an integer from 1 to 9, preferably q is 1; D, B, and X are as defined with respect to Equation I.
[0008] According to a third aspect, the present invention provides the use of the above-mentioned nickel-cobalt-lithium selective adsorbent for adsorbing metals, wherein the metal is any one of nickel, cobalt, and lithium, or a combination of nickel and cobalt.
[0009] According to a fourth aspect, the present invention provides an extractant for solid-phase extraction of metal elements, characterized in that it contains the above-mentioned nickel-cobalt-lithium selective adsorbent.
[0010] According to a fifth aspect, the present invention provides a method for extracting lithium from sodium-containing brine, characterized in that an extractant containing the above-mentioned nickel-cobalt-lithium selective adsorbent is used, and the initial aqueous phase pH is controlled to be 9-13.5.
[0011] According to a sixth aspect, the present invention provides a method for solid-phase extraction of metal elements, characterized in that an extractant containing the above-mentioned nickel-cobalt-lithium selective adsorbent is used, wherein the metal is any one of nickel and cobalt or a combination of nickel and cobalt.
[0012] The nickel-cobalt-lithium selective adsorbent of the present invention exhibits high selectivity for nickel, cobalt, and lithium, is simple to prepare, and is effective in separation and purification. It is also environmentally friendly and low in cost. Detailed Implementation
[0013] The various aspects of the invention, as well as further objects, features and advantages, will be described in more detail below.
[0014] Nickel-cobalt-lithium selective adsorbent According to a first aspect, the present invention provides a nickel-cobalt-lithium selective adsorbent, characterized in that it has the structure shown in Formula I: (Equation I) in: M is the resin matrix; A is selected from -O- and -NH-(CH2). t - and -NH(CH2) n NH-, where n is an integer from 2 to 9, and t is an integer from 0 to 9; B is either C or S=O; X is C, CH, or N; D, together with B and X, can form a saturated or unsaturated ring structure containing one or two heteroatoms, or a benzo[a] ring structure. The ring structure or benzo[a] ring structure is optionally composed of one or more elements selected from C1-C2. 20 Alkyl, C1-C 20 Alkoxy, C6-C 12 Aryl, optional C1-C 20 The groups that replace amino, hydroxyl, fluorine and chlorine atoms are selected from N, O and S heteroatoms, and the ring structure is a 5, 6 or 7-membered ring structure.
[0015] The present invention does not specifically limit the resin matrix M. Preferably, the resin matrix M is selected from polystyrene resin, copolymer of styrene and divinylbenzene, phenolic resin, polyacrylic acid resin, and silicone resin. More preferably, the resin matrix M is selected from polystyrene resin and copolymer of styrene and divinylbenzene.
[0016] Preferably, the cyclic structure or benzocyclic structure is optionally substituted with one or two groups selected from C1-C8 alkyl, C1-C8 alkoxy, phenyl, optionally C1-C8 substituted amino, hydroxyl, fluorine and chlorine atoms.
[0017] Specifically, n is 2, 3, 4, 5, 6, 7, 8 or 9, and t is 1, 2, 3, 4, 5, 6, 7, 8 or 9, preferably n is 2 and t is 0, 1 or 2.
[0018] Preferably, D, B, and X form the structure shown below: , , , , , , , , , , , , , , , , , and , * indicates a connection site.
[0019] More preferably, D, B, and X form a structure as shown below: , , , , , , and , * indicates a connection site.
[0020] Preferably, the nickel-cobalt-lithium selective adsorbent has a structure selected from the following: , , , , , , , , , , , , , , , , , , , , , , , , , , , , , , , , , and , M is selected from polystyrene resin, copolymer of styrene and divinylbenzene, phenolic resin, polyacrylic resin and silicone resin.
[0021] More preferably, the nickel-cobalt-lithium selective adsorbent has a structure selected from the following: , , , , , , , , and , M is selected from polystyrene resin and copolymers of styrene and divinylbenzene.
[0022] The nickel-cobalt-lithium selective adsorbent obtained according to the present invention has high selectivity for metal elements (especially nickel, cobalt, and lithium), and can adsorb metal elements such as nickel and cobalt in acidic solutions and lithium in alkaline solutions, providing a new extractant for extraction and purification processes.
[0023] Method for preparing the above-mentioned nickel-cobalt-lithium selective adsorbent According to a second aspect, the present invention provides a method for preparing the above-mentioned nickel-cobalt-lithium selective adsorbent, characterized in that it includes one of the following steps S1, S2, S3, S4, and S5: S1. A resin containing primary amine groups is reacted with a compound of Formula II in the presence of a catalyst at a temperature of 40-120°C via an amine-ester exchange reaction to obtain the nickel-cobalt-lithium selective adsorbent. (Formula II) in: Y is C1-C 10 alkoxy groups; D, B, and X are as defined with respect to equation I. S2. In an acidic solution in the presence of aldehydes, the primary amine resin is reacted with a ketone of formula III at a temperature of 40-120°C to obtain the nickel-cobalt-lithium selective adsorbent. (Formula III) in: D, B, and X are as defined with respect to equation I. S3. First, H2N-(CH2)n-NH2 is subjected to an amine-ester exchange reaction with the compound of formula II to obtain the intermediate of formula IV. Then, the chlorinated resin is subjected to a substitution reaction with the intermediate of formula IV to obtain the nickel-cobalt-lithium selective adsorbent. (Formula IV) in: n is defined for equation I. D, B, and X are as defined with respect to equation I. S4. Add alkaline solution to the reaction vessel containing the swollen chlorine bead resin, heat to induce a hydrolysis reaction, separate the resin after the reaction, wash repeatedly with solvent to obtain the hydrolyzed chlorine beads, place the hydrolyzed chlorine bead resin in a reaction vessel, add a solvent to swell the chlorine bead resin, a compound of formula II, an acid-binding agent, and a co-catalyst, heat under reflux to induce a substitution reaction, and obtain the nickel-cobalt-lithium selective adsorbent, wherein the compound of formula II is as defined in step S1. S5. A substitution reaction is carried out between the resin containing primary amine groups and the compound of formula V in an alkaline solution under heating conditions to obtain the nickel-cobalt-lithium selective adsorbent. in: (Form V) in: Y is either Cl or Br; q is an integer from 1 to 9, preferably q is 1; D, B, and X are as defined with respect to Equation I.
[0024] Before steps S1, S2, S3, S4, and S5, the resin matrix can be pretreated.
[0025] Specifically, the pretreatment includes rinsing the resin matrix with a solvent, stirring and shaking the resin, and then removing excess solvent.
[0026] Preferably, the solvent used in the pretreatment is a mixture of one or more solvents selected from water, ethanol, diethyl ether, toluene, dioxane, N,N-dimethylformamide, dichloromethane, and ethyl acetate.
[0027] In some embodiments, the preparation method includes step S1.
[0028] Preferably, the compound of Formula II is selected from 2,6-dioxoethyl cyclohexanecarboxylate, methyl 2,4-dioxapyrrolidine-3-carboxylate, ethyl 4-hydroxy-2-oxo-2,5-dihydro-3-furanoate, etc. , 3-Methyl-5-oxo-1-phenyl-4,5-dihydro-1H-pyrazole-4-carboxylic acid ethyl ester, 2-oxo-2,3-dihydro-1H-imidazol-1-carboxylic acid tert-butyl ester, , , 2-O-indene-1-carboxylic acid methyl ester, 1H-indene-2-carboxylic acid, 2,3-dihydro-1-oxo-methyl ester or .
[0029] More preferably, the compound of Formula II is selected from methyl 2,4-dioxapyrrolidine-3-carboxylate, ethyl 4-hydroxy-2-oxo-2,5-dihydro-3-furanoate, , 3-Methyl-5-oxo-1-phenyl-4,5-dihydro-1H-pyrazole-4-carboxylic acid ethyl ester , or .
[0030] Preferably, the catalyst is 4-dimethylaminopyridine.
[0031] Preferably, the molar ratio of the primary amine group of the resin matrix, the compound of formula II, and the catalyst is 1:(1-1.5):(0.1-0.5).
[0032] Preferably, the amine-ester exchange reaction is carried out in a solvent selected from one or more solvents chosen from methanol, ethanol, diethyl ether, toluene, dioxane, N,N-dimethylformamide, dichloromethane, and ethyl acetate.
[0033] Preferably, the amount of solvent used in the amine transesterification reaction is 1-30 times the mass of the resin.
[0034] Preferably, the amine-lipid exchange reaction is carried out at a temperature in the range of 60-120°C.
[0035] Preferably, the time for the amine-lipid exchange reaction is 2-48 hours.
[0036] In some embodiments, the preparation method includes step S2.
[0037] Preferably, in step S2, the acid in the acidic solution is one or a mixture of sulfuric acid, hydrochloric acid, nitric acid, phosphoric acid, and perchloric acid.
[0038] Preferably, in step S2, the solvent in the acidic solution is one or a mixture of water, ethanol, methanol, and N,N-dimethylformamide.
[0039] Preferably, in step S2, the concentration of the acidic solution is 0.1-6 mol / L.
[0040] Preferably, in step S2, the aldehyde is any one or a mixture of formaldehyde, benzaldehyde, and C1-C9 alkyl formaldehyde.
[0041] More preferably, in step S2, the aldehyde is any one or a mixture of formaldehyde, acetaldehyde, propionaldehyde, and benzaldehyde.
[0042] More preferably, in step S2, the aldehyde is selected from formaldehyde.
[0043] Preferably, the ketones of Formula III are selected from 3-acetyl-2-oxazolone, 2-acetyl-1-indanone, dehydroacetic acid, and .
[0044] Preferably, the ratio of the amount of acid in the acidic solution to the molar amount of primary amine groups in the resin is 0.5-3:1.
[0045] Preferably, the molar ratio of the primary amine groups, aldehydes and ketones of Formula III in the resin matrix is 1:1-1.5:0.75-1.75, more preferably 1:1-1.25:0.8-1.5.
[0046] Preferably, the amount of solvent in the acidic solution is 1-30 times the mass of the resin.
[0047] Preferably, in step S2, the reaction time is 4-48 hours.
[0048] In some embodiments, the preparation method includes step S3.
[0049] Preferably, the conditions for the amino-lipid exchange reaction in step S3 are the same as those in step S1.
[0050] Preferably, H2N-(CH2) n The molar ratio of -NH2 to the compound of formula II is 1.1-1.5:1.
[0051] The "chloro-2-methyl resin" mentioned in this application refers to a resin containing a chloromethyl (-CH2Cl) functional group.
[0052] Preferably, the reaction in step S3 is carried out in an alkaline solution at a temperature of 40-120°C.
[0053] Preferably, the solute in the alkaline solution in step S3 is one or a combination of two or more of sodium hydroxide, potassium hydroxide, sodium carbonate, potassium carbonate, sodium bicarbonate, ammonia, triethylamine, and calcium hydroxide.
[0054] Preferably, the solvent of the alkaline solution in step S3 is one or a combination of two or more of water, ethanol, methanol, and N,N-dimethylformamide.
[0055] Preferably, the concentration of the alkaline solution in step S3 is 0.1-5 mol / L.
[0056] The molar ratio of the chlorinated resin and the substance of formula IV mentioned in step S3 is 1:(1.2-3).
[0057] Preferably, the amount of solvent used in the alkaline solution in step S3 is 1-30 times the mass of the resin.
[0058] Preferably, the reaction time in step S3 is 4-48 hours.
[0059] In some embodiments, the preparation method includes step S4.
[0060] Preferably, the solvent used to swell the chloroform resin in step S4 is any one of acetone, ethanol, 1,4-dioxane, dichloromethane, dimethyl sulfoxide, N,N-dimethylformamide, benzene, and diethyl ether.
[0061] More preferably, the solvent is acetone.
[0062] Preferably, the swelling time in step S4 is 6-12 hours, and more preferably 10 hours.
[0063] Preferably, the solvent used for washing in the hydrolysis reaction described in step S4 is any one or a mixture of several of anhydrous ethanol, dichloromethane, methanol, n-hexane, deionized water, 1,4-dioxane, and acetone, with anhydrous ethanol and acetone being the most preferred.
[0064] Preferably, the alkaline solution in step S4 is either a sodium hydroxide solution or a potassium hydroxide solution, and more preferably, the alkaline solution is a sodium hydroxide solution.
[0065] Preferably, the concentration of the sodium hydroxide solution or potassium hydroxide solution in step S4 is 1-4 mol / L, more preferably 2-3 mol / L.
[0066] Preferably, the hydrolysis reaction in step S4 is carried out at a temperature of 40-90°C for 8-24 hours; more preferably, the temperature is 50°C and the reaction time is 12 hours.
[0067] Preferably, the acid-binding agent in step S4 is any one of potassium carbonate, sodium carbonate, triethylamine, tri-n-propylamine, and N,N-diisopropylethylamine.
[0068] Potassium carbonate is the preferred acid-binding agent.
[0069] Preferably, the co-catalyst in step S4 includes potassium iodide and / or tetrabutylammonium chloride.
[0070] Preferably, the molar ratio of the chlorinated resin, the compound of formula II, and the acid binder in step S4 is 1:(1.5-3):(1-2).
[0071] More preferably, the feeding ratio is 1:2:1.5.
[0072] Preferably, the amounts of potassium iodide and tetrabutylammonium chloride are both catalyst equivalents.
[0073] Preferably, the substitution reaction in step S4 is carried out at a reaction temperature of 60-100°C for 8-24 hours; more preferably, the temperature is 80°C and the reaction time is 12 hours.
[0074] In some embodiments, the preparation method includes step S5.
[0075] Preferably, the solute, solvent, and concentration of the alkaline solution in step S5 are as described with respect to step S3.
[0076] Preferably, the ratio of the amount of solute in the alkaline solution to the molar amount of primary amine groups in the resin in step S5 is 0.8-2.5:1.
[0077] Preferably, the ratio of the primary amine group content of the resin to the molar amount of compound V in step S5 is 1:0.75-1.75, more preferably 1:0.8-1.5.
[0078] Preferably, the amount of solvent and the reaction time in step S5 are as described for step S3.
[0079] Preferably, the preparation method includes washing the nickel-cobalt-lithium selective adsorbent with anhydrous ethanol and / or acetone.
[0080] Preferably, the resin matrix is a macroporous resin.
[0081] As used herein, the pore size of the macroporous resin is in the range of 10-1000 nm, preferably 20-100 nm.
[0082] The preparation method of the present invention can effectively prepare the nickel-cobalt-lithium selective adsorbent of the present invention.
[0083] Applications of nickel-cobalt-lithium selective adsorbents for adsorbing metals According to a third aspect, the present invention provides the use of the above-mentioned nickel-cobalt-lithium selective adsorbent for adsorbing metals, wherein the metal is any one of nickel, cobalt, and lithium, or a combination of nickel and cobalt.
[0084] The nickel-cobalt-lithium selective adsorbent can be used to adsorb metals in hydrometallurgy and wastewater treatment industries.
[0085] According to a fourth aspect, the present invention provides an extractant for solid-phase extraction of metal elements, characterized in that it contains the above-mentioned nickel-cobalt-lithium selective adsorbent.
[0086] According to a fifth aspect, the present invention provides a method for extracting lithium from sodium-containing brine, characterized in that an extractant containing the above-mentioned nickel-cobalt-lithium selective adsorbent is used, and the initial aqueous phase pH is controlled to be 9-13.5, preferably 10-13.5, and more preferably 11-13.
[0087] According to a sixth aspect, the present invention provides a method for solid-phase extraction of metal elements, characterized in that an extractant containing the above-mentioned nickel-cobalt-lithium selective adsorbent is used, wherein the metal is any one of nickel and cobalt or a combination of nickel and cobalt.
[0088] The nickel-cobalt-lithium selective adsorbent of the present invention can effectively adsorb nickel, cobalt, lithium and the like.
[0089] In some embodiments, the method for solid-phase extraction of metal elements includes the following steps: S11: The above nickel-cobalt-lithium selective adsorbent is contacted with a solution containing nickel, cobalt, calcium and / or magnesium for extraction, and then solid-liquid separation is performed to obtain nickel-cobalt-lithium selective adsorbent loaded with nickel and cobalt and raffinate. S12: The nickel- and cobalt-loaded adsorbent is first back-extracted using an acid solution, followed by solid-liquid separation to obtain the back-extracted adsorbent and the nickel- and cobalt back-extracted solution.
[0090] The solution containing nickel, cobalt, calcium and / or magnesium contains one or a combination of two of nickel and cobalt.
[0091] Advantageously, the extraction time is 1 min or more, for example 1-120 min, for example 5-100 min, for example 10-80 min, preferably 10-60 min.
[0092] Advantageously, the pH of the nickel, cobalt, calcium and / or magnesium-containing solution is 1.5-4.5, for example 2-4, for example 2-3.5.
[0093] Advantageously, the nickel-cobalt-lithium selective adsorbent loaded with nickel and cobalt is washed with an acid solution before back-extraction to remove impurity metals.
[0094] Advantageously, the acid solution used for washing is selected from sulfuric acid solution and hydrochloric acid solution, and the pH value of the acid solution used for washing is between 1 and 2.5, for example 1.5-2.
[0095] In other embodiments, the method for extracting lithium from high-sodium brine includes the following steps: S21: The above-mentioned nickel-cobalt-lithium selective adsorbent is contacted with a lithium-containing sodium solution for extraction, and then solid-liquid separation is performed to obtain lithium-loaded adsorbent and raffinate. S22: The lithium-loaded adsorbent is subjected to a second back-extraction using an acid solution, followed by solid-liquid separation to obtain the back-extracted adsorbent and lithium back-extraction solution.
[0096] Advantageously, the lithium-containing sodium solution contains 0.1-5 g / L of lithium and 0.1-120 g / L of sodium, with a sodium-lithium ratio ≤500:1.
[0097] Advantageously, the extraction time is 1 min or more, for example 1-120 min, for example 5-100 min, for example 10-80 min, preferably 10-60 min.
[0098] Advantageously, the lithium-loaded adsorbent is washed with water before the second back-extraction to remove sodium.
[0099] Advantageously, the acid solutions used for the first and second back-extractions are each independently selected from sulfuric acid solution and / or hydrochloric acid solution. Preferably, the concentration of the sulfuric acid solution used for the back-extractions is 0.5-6 mol / L and the concentration of the hydrochloric acid solution is 1-8 mol / L.
[0100] In some embodiments, the method further includes pretreatment of the nickel-cobalt-lithium selective adsorbent, namely, mixing the nickel-cobalt-lithium selective adsorbent with a 1-2 mol / L sulfuric acid or hydrochloric acid solution and stirring, then washing with pure water until the supernatant is colorless, then washing with a 0.2-1 mol / L, preferably 0.2-0.5 mol / L sodium hydroxide or potassium hydroxide solution until the supernatant is alkaline, then washing the resin with pure water until neutral, and filtering to obtain the pretreated resin for use.
[0101] The nickel-cobalt-lithium selective adsorbent of this invention operates in an alkaline environment with a pH of 9-13.5, preferably 10-13.5, in Na+. + / Li + Achieving a mass ratio within the range of 10-500:1: when Na + / Li+ When the mass ratio is >100:1, the lithium-sodium separation coefficient βLi / Na ≥15.0; Na + / Li + When the mass ratio is 10-100:1, the lithium-sodium separation coefficient is ≥18.0.
[0102] The nickel-cobalt-lithium selective adsorbent of the present invention improves the selectivity for metal elements, especially nickel, cobalt and lithium, and can effectively separate nickel and cobalt from calcium and magnesium impurities, and effectively separate lithium from sodium.
[0103] The "selectivity" mentioned in this application refers to the separation coefficient of the metallic elements. β Furthermore, the separation coefficient is derived from the following formula: β A / B =D A / D B In the formula, D A This represents the ratio of the content of metal element A in the resin to the content of metal element A in the raffinate aqueous phase after one extraction. D B This represents the ratio of the content of metal element B in the resin to the content of metal element B in the raffinate aqueous phase after one extraction.
[0104] In this application, the terms "comprising" and "including" cover situations where other elements not explicitly mentioned are also included, as well as situations where the mentioned elements constitute the entirety of the application.
[0105] Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. In the event of any discrepancy between the definitions of terms in this specification and their commonly understood meaning by one of ordinary skill in the art to which this invention pertains, the definitions set forth herein shall prevail.
[0106] Unless otherwise stated, all numerical values for the amount of ingredients, temperature, time, etc., used in the specification and claims are to be understood as being modified by the term "about". Therefore, unless otherwise indicated, the numerical parameters set forth herein are approximate values that can be varied to obtain the desired performance.
[0107] Example The following will further illustrate the concept and technical effects of the present invention with reference to embodiments, so that those skilled in the art can fully understand the purpose, features, and effects of the present invention. It will be readily understood by those skilled in the art that the embodiments described herein are merely illustrative, and the scope of the present invention is not limited thereto.
[0108] Example 1: Preparation of Resin 1 The synthetic route for resin 1 is shown below: (Resin 1) Add 10 g (30 mmol, -NH2) of primary amine polystyrene resin (from Samsung Resins, model SX382) and 7.18 g (35 mmol) of... to a three-necked flask. (CAS No.: 43015-71-0) 0.48 g (4 mmol) of 4-dimethylaminopyridine, and then 50 mL of N,N-dimethylformamide were added. The mixture was heated at 100 °C for 12 hours under mechanical stirring. After the reaction was completed, the resin was separated and washed repeatedly with anhydrous ethanol and acetone to obtain resin 1.
[0109] Example 2: Preparation of Resin 2 The synthetic route for resin 2 is shown below: (Resin 2) 10 g (30 mmol, -NH2) of primary amine polystyrene resin (from Samsung Resin, model SX382), 5.5 g (35 mmol) of methyl 2,4-dioxapyrrolidine-3-carboxylic acid, and 0.48 g (4 mmol) of 4-dimethylaminopyridine were added to a three-necked flask, followed by 50 mL of toluene. The mixture was heated at 80 °C for 24 hours under mechanical stirring. After the reaction was completed, the resin was separated and washed repeatedly with anhydrous ethanol and acetone to obtain resin 2.
[0110] Example 3: Preparation of Resin 3 The synthetic route for resin 3 is shown below: (Resin 3) Add 10g (30mmol, -NH2) primary amine polystyrene resin (from Samsung Resins, model SX382) and 7.2g (35mmol) of [unclear text - likely a continuation of a previous sentence] to a three-necked flask. (CAS No.: 82131-00-8) 0.48 g (4 mmol) of 4-dimethylaminopyridine, and then 100 mL of N,N-dimethylformamide were added. The mixture was heated at 100 °C for 12 hours under mechanical stirring. After the reaction was completed, the resin was separated and washed repeatedly with anhydrous ethanol and acetone to obtain resin 3.
[0111] Example 4: Preparation of Resin 4 The synthetic route for resin 4 is shown below: (Resin 4) Specifically, 10 g (30 mmol, -NH2) and 8.5 g (45 mmol) of primary amino polystyrene microspheres (from Samsung Resin, model SX382) were taken. (CAS No.: 185746-06-9) was placed in a 100ml three-necked flask, and 57g of acetone and 4.6g (45mmol) of triethylamine were added in sequence. The mixture was heated to 60℃ under mechanical stirring and reacted for 4 hours. After the reaction was completed, the resin was separated and washed repeatedly with anhydrous ethanol and acetone to obtain resin 4.
[0112] Example 5: Preparation of Resin 5 The synthetic route for resin 5 is shown below: (Resin 5) Add 10g (30mmol, -NH2) primary amine polystyrene resin (from Samsung Resins, model SX382) and 8.2g (35mmol) of [unclear text - likely a continuation of the previous sentence] to a three-necked flask. (CAS No.: 1084-41-9) 0.48 g (4 mmol) of 4-dimethylaminopyridine, and then 100 mL of N,N-dimethylformamide were added. The mixture was heated at 100 °C for 12 hours under mechanical stirring. After the reaction was completed, the resin was separated and washed repeatedly with anhydrous ethanol and acetone to obtain resin 5.
[0113] Example 6: Preparation of Resin 6 The synthetic route for resin 6 is shown below: (Resin 6) Add 10 g (30 mmol, -NH2) of primary amine polystyrene resin (from Samsung Resin, model SX382) and 5.89 g (35 mmol) of... to a three-necked flask. (CAS No.: 78600-90-5), 0.48 g (4 mmol) of 4-dimethylaminopyridine and 6.2 g (40 mmol) of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide, and then 100 mL of N,N-dimethylformamide were added. The mixture was heated at 100 °C for 12 hours under mechanical stirring. After the reaction was completed, the resin was separated and washed repeatedly with anhydrous ethanol and acetone to obtain resin 6.
[0114] Example 7: Preparation of Resin 7 The synthetic route for resin 7 is shown below: (Resin 7) 10 g (30 mmol, -NH2) of primary amine polystyrene resin (from Samsung Resin, model SX382), 6.0 g (35 mmol) of ethyl 4-hydroxy-2-oxo-2,5-dihydro-3-furanose, and 0.48 g (4 mmol) of 4-dimethylaminopyridine were added to a three-necked flask, followed by 100 mL of N,N-dimethylformamide. The mixture was heated at 100 °C for 12 hours under mechanical stirring. After the reaction was completed, the resin was separated and washed repeatedly with anhydrous ethanol and acetone to obtain resin 7.
[0115] Example 8: Preparation of Resin 8 The synthetic route for resin 8 is shown below: Add 5.2g of ethylenediamine and 14.8g (72mmol) of [unspecified ingredient] to a three-necked flask. 0.96 g (8 mmol) of 4-dimethylaminopyridine was added, followed by 100 mL of N,N-dimethylformamide. The mixture was heated at 80 °C for 8 hours under mechanical stirring to obtain... Intermediate.
[0116] Then take 10 g (50 mmol) of intermediate and chlorinated globulin resin (the preparation method of chlorinated globulin resin is described in CN101781379B, purchased from Zhejiang Zhengguang Industrial Co., Ltd.) were placed in a 100 ml three-necked flask, and 60 g of N,N-dimethylformamide and 7.27 g (72 mmol) of triethylamine were added sequentially. The mixture was heated to 50 °C under mechanical stirring and reacted for 8 hours. After the reaction was completed, the resin was separated and washed repeatedly with anhydrous ethanol and acetone to obtain resin 8.
[0117] Example 9: Preparation of Resin 9 The synthetic route for resin 9 is shown below: (Resin 9) In a 250 mL three-necked flask, 30 g of chlorinated resin was added and swollen thoroughly with 100 mL of dichloromethane for 12 h. Then, the swollen chlorinated resin was transferred to another 250 mL three-necked flask, and 100 mL of 2 mol / L sodium hydroxide solution was added. The mixture was reacted at 50 °C for 12 h. After the reaction was completed, the resin was separated and washed twice with 100 mL of anhydrous ethanol to obtain the hydrolyzed chlorinated resin.
[0118] Place the hydrolyzed chlorine bulbs in a 250 mL three-necked flask, add 100 mL of anhydrous ethanol, and then add 22.6 g of the solution. 6.22 g of anhydrous potassium carbonate, 0.2 g of potassium iodide, and 1 drop of tetrabutylammonium chloride were heated under reflux for 12 h to obtain resin 9.
[0119] Example 10 The properties of the resin obtained above were tested as described below: Pretreatment: The resin was mixed with 2 mol / L sulfuric acid and stirred at 250 rpm for 30 min. It was then washed with pure water until the supernatant was colorless. After that, it was washed with 0.25 mol / L sodium hydroxide solution until the supernatant was alkaline. The resin was then washed with pure water until it was neutral. The pretreated resin was then filtered for later use. The mixture contains 0.1 g / L Li and 40 g / L Na (Na + / Li + Sulfate solutions with a mass ratio of 400:1 and pH values of 10, 11, 12, 13, and 13.5 were used as the initial aqueous phase. Then, 30 mL of the initial aqueous phase was mixed with 10 g of pretreated resin and shaken at room temperature for 60 min. After extraction, solid-liquid separation was performed to obtain the raffinate aqueous phase and the lithium-loaded resin. The concentration of each metal element in the raffinate aqueous phase was determined by inductively coupled plasma atomic emission spectrometry (ICP). The content of each metal element in the lithium-loaded resin was determined by the difference method. The results are summarized in Table 1.
[0120] Table 1. Metal element content and separation coefficient in the raffinate of each resin Table 1 shows that within the pH range of 10-13.5, based on an initial Li concentration of 0.1 g / L, the lithium adsorption rate reaches 56%-80%, and the Li / Na separation coefficient remains stable between 17.6-35.0. Specifically, at pH 12 and Na... + / Li + Under conditions where the mass ratio is >100:1, the lithium-sodium separation coefficient βLi / Na ≥25.0. Each resin exhibits specific selectivity for lithium within the pH range of 10-13.5, making them suitable for the selective adsorption and separation of lithium in low-lithium, high-sodium solutions.
[0121] The resin was back-extracted three times using 30 mL of 2.5 mol / L hydrochloric acid solution to separate the solid and liquid phases, yielding the back-extracted resin.
[0122] Example 11 The properties of the back-extraction resin in Example 10 were tested as described below: The back-extracted resin described in Example 10 was washed three times with 30 mL of pure water, and then washed with 0.25 mol / L sodium hydroxide solution until the supernatant was alkaline. After that, it was washed with pure water until it was neutral to obtain the regenerated resin after transformation for later use.
[0123] A sulfate solution containing 3.5 g / L Li and with a pH of 12 was prepared as the initial aqueous phase. 2 g of the regenerated resin after transformation was placed in each beaker, and 60 mL of the prepared initial aqueous phase was added. The mixture was shaken and extracted at room temperature for 60 min. After extraction, solid-liquid separation was performed to obtain the raffinate aqueous phase. The lithium concentration in the raffinate aqueous phase was determined by inductively coupled plasma atomic emission spectrometry (ICP). The lithium content in the back-extracted resin was calculated using the difference method to obtain the lithium loading of the back-extracted resin. The results are summarized in Table 2.
[0124] Table 2. Lithium loading of the resin after back-extraction As shown in Table 2, the lithium loading of each resin after back-extraction and regeneration ranged from 6.8 to 7.6 mg / g, indicating that the lithium loading of the resin is ≥6.5 mg / g under pH=12 conditions. After 10 cycles, the loading did not decrease significantly, indicating that the resin has excellent regeneration stability.
[0125] Example 12 The resin properties were tested as described below: The resin was pretreated according to Example 10.
[0126] Configuration containing Ni 2+ Co 2+ Ca 2+ Mg 2+ Sulfate solutions of 0.05 g / L each with pH values of 1.5, 2.0, 2.5, 3.0, and 3.5 were used as the initial aqueous phase. Then, 30 mL of the initial aqueous phase was mixed with 5 g of pretreated resin and shaken at room temperature for 60 min. After extraction, the concentration of each metal element in the raffinate was determined by inductively coupled plasma atomic emission spectrometry (ICP). The content of metal elements in the resin was calculated by difference. The results are summarized in Table 3.
[0127] Table 3. Metal element content in the raffinate of each resin Table 3 shows that the primary adsorption rates of each resin for nickel and cobalt are greater than 80% and 60%, respectively, while their adsorption of calcium and magnesium is weak. Calculations show that at pH 2.5, the separation coefficients for nickel and calcium, and cobalt and magnesium, are 103 and 71, respectively. Each adsorbent exhibits specific selectivity for nickel and cobalt within the pH range of 1.5-3.5, making them suitable for the selective adsorption and separation of nickel and cobalt in solutions containing nickel, cobalt, calcium, and magnesium.
[0128] Example 13 The test was conducted according to Example 10, except that the Li concentration was 0.1 g / L, and the Na ion concentrations were changed to 1 g, 2 g / L, 5 g / L, and 10 g / L, with a pH of 12 in each case, as the initial aqueous phase. 30 mL of the initial aqueous phase was mixed with 10 g of the pretreated resin and shaken at room temperature for 60 min. The test results are summarized in Table 4.
[0129] Table 4. Performance data of resin 4 under different sodium-lithium ratios As shown in Table 4, in Na + / Li + Within a mass ratio range of 10:1 to 100:1, the lithium adsorption rate remained stable between 81% and 89%, and the βLi / Na ratio remained in a high selectivity range of 38.4 to 65.5. This example confirms that the adsorbent exhibits high selectivity over a wide range of Na... + / Li + Excellent performance is maintained at mass ratios (10:1-100:1).
[0130] Comparative Example 1 Resin 10 was prepared according to the following synthetic route: (Resin 10) 10 g of primary amine polystyrene resin (from Samsung Resin, model SX382), 4.1 g (35 mmol) of methyl acetoacetate and 0.48 g (4 mmol) of 4-dimethylaminopyridine were added to a three-necked flask, followed by 100 mL of N,N-dimethylformamide. The mixture was heated to 80 °C for 24 hours under mechanical stirring. After the reaction was completed, the resin was separated and washed repeatedly with anhydrous ethanol and acetone to obtain resin 10.
[0131] The test was conducted according to Example 10, except that the initial aqueous phase pH was 11, and the resin's structural formula was [insert structural formula here]. M represents polystyrene microspheres, i.e., resin 10.
[0132] The results showed that the separation coefficient of lithium and sodium by resin 10 was 1.4, indicating poor separation effect between lithium and sodium.
[0133] Comparative Example 2 Resin 11 was prepared according to the following synthetic route: (Resin 11) 10 g of primary amine polystyrene resin (from Samsung Resin, model SX382), 5.0 g (35 mmol) of methyl 2-oxopyrrolidine-3-carboxylate, and 0.48 g (4 mmol) of 4-dimethylaminopyridine were added to a three-necked flask. Then, 100 mL of N,N-dimethylformamide was added. The mixture was heated to 80 °C for 24 hours under mechanical stirring. After the reaction was completed, the resin was separated and washed repeatedly with anhydrous ethanol and acetone to obtain resin 11.
[0134] The test was conducted according to Example 10, except that the initial aqueous phase pH was 11, and the resin's structural formula was [insert structural formula here]. M represents polystyrene microspheres, i.e., resin 11.
[0135] The results showed that the separation coefficient of lithium and sodium by resin 11 was 2.1, indicating poor separation effect between lithium and sodium.
[0136] Comparative Example 3 Resin 12 was prepared according to the following synthetic route: (Resin 12) Take 10 g (30 mmol, -NH2) primary amine polystyrene resin (from Samsung Resin, model SX382), 6.8 g (72 mmol) chloroacetic acid and 7.6 g (72 mmol) sodium carbonate and place them in a 100 ml three-necked flask. Add 50 mL of water and heat at 80 °C for 12 hours under mechanical stirring. After the reaction is complete, separate the resin and wash it repeatedly with anhydrous ethanol and acetone to obtain resin 12.
[0137] The test was conducted with reference to Example 12, except that the initial aqueous phase pH was 2.5 and the resin was Resin 12.
[0138] The results showed that the contents of nickel, cobalt, calcium, and magnesium in the raffinate were 0.013 g / L, 0.02 g / L, 0.03 g / L, and 0.036 g / L, respectively, indicating poor separation of nickel and cobalt from calcium and magnesium.
[0139] Comparative Example 4 The resin 10 was tested according to Example 12, except that the initial aqueous phase pH was 3.0 and the resin was resin 10.
[0140] The results showed that the contents of nickel, cobalt, calcium, and magnesium in the raffinate were 0.036 g / L, 0.04 g / L, 0.045 g / L, and 0.049 g / L, respectively, indicating poor separation of nickel and cobalt from calcium and magnesium.
[0141] Comparative Example 5 Resin 1 was tested according to Example 10, except that the initial aqueous phase pH value was 9.
[0142] The results showed that the selectivity coefficients of resin 1 for lithium and sodium were 15.7, which met the requirements for industrial-grade lithium extraction (β>15).
[0143] Comparative Example 6 The first component is 2-hydroxy-4-n-octyloxybenzophenone, with an addition amount of 0.05 mol; the second component is sulfonated kerosene, with an addition amount of 1 liter. After mixing until homogeneous, it is used as the organic phase for lithium extraction.
[0144] The organic phase used for lithium extraction was tested according to Example 10. The difference from Example 10 was that the initial pH value of the aqueous phase was 9, 10, 11, 12, 13, and 13.5. The extraction operation conditions were: 20 mL of organic phase, 20 mL of aqueous phase, O / A ratio of 1:1, room temperature, in a separatory funnel, shaken for 60 minutes, phase separation for 10 minutes, and the elution residue was taken for ion concentration analysis.
[0145] The results showed that the lithium concentrations in the raffinate were 0.074, 0.069 g / L, 0.053 g / L, 0.044 g / L, 0.032 g / L, and 0.027 g / L, respectively, and the sodium concentrations were 35.7 g / L, 35.2 g / L, 34.4 g / L, 33.2 g / L, 32.8 g / L, and 32.1 g / L, respectively. The lithium / sodium separation coefficients βLi / Na were 2.9, 3.3, 5.4, 6.2, 9.5, and 11.0, respectively. Even at the optimal pH of 13.5, the conventional extractant had a β(Li / Na) value of 11.0, which was significantly lower than the β value of the resin of this invention under the same pH conditions.
[0146] The lithium-loaded organic phase was back-extracted with 2.5 mol / L hydrochloric acid solution and reused. After 10 cycles, under the condition of an initial pH of 9, the lithium / sodium separation coefficient of the organic phase in this embodiment decreased from the initial 2.9 to 2.4, while the separation coefficient of resin 1 of the present invention decreased from 15.7 to 15.3 under the same conditions (pH=9). This shows that the resin of the present invention is more stable than organic solvents.
[0147] The foregoing descriptions are merely exemplary embodiments or examples of the present invention and are not intended to limit the invention. Those skilled in the art will recognize that the present invention can be modified and varied in many ways. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principle of the present invention are included within the scope of the claims of this application.
Claims
1. A nickel-cobalt-lithium selective adsorbent, characterized in that, It has the structure of Formula I: (Equation I) in: M is the resin matrix; A is selected from -O- and -NH-(CH2). t - and -NH(CH2) n NH-, where n is an integer from 2 to 9, and t is an integer from 0 to 9; B is either C or S=O; X is C, CH, or N; D, together with B and X, can form a saturated or unsaturated ring structure containing one or two heteroatoms, or a benzo[a] ring structure. The ring structure or benzo[a] ring structure is optionally composed of one or more elements selected from C1-C2. 20 Alkyl, C1-C 20 Alkoxy, C6-C 12 Aryl, optional C1-C 20 The groups that replace amino, hydroxyl, fluorine and chlorine atoms are selected from N, O and S heteroatoms, and the ring structure is a 5, 6 or 7-membered ring structure.
2. The nickel-cobalt-lithium selective adsorbent according to claim 1, characterized in that, M is selected from any one or more of polystyrene resin, copolymer of styrene and divinylbenzene, phenolic resin, polyacrylic resin, and silicone resin.
3. The nickel-cobalt-lithium selective adsorbent according to claim 1 or 2, characterized in that... D, B, and X together form a structure as shown below: , , , , , , , , , , , , , , , , , and , * indicates a connection site.
4. The nickel-cobalt-lithium selective adsorbent according to claim 3, characterized in that, It has a structure selected from the following: , , , , , , , , , , , , , , , , , , , , , , , , , , , , , , , , , and , M is selected from polystyrene resin, copolymer of styrene and divinylbenzene, phenolic resin, polyacrylic resin and silicone resin.
5. The use of the nickel-cobalt-lithium selective adsorbent according to any one of claims 1-4 for adsorbing metals, wherein the metal is any one of nickel, cobalt, and lithium, or a combination of nickel and cobalt.
6. An extractant for solid-phase extraction of metal elements, characterized in that, The nickel-cobalt-lithium selective adsorbent contains any one of claims 1-4.
7. A method for solid-phase extraction of metallic elements, characterized in that, The extractant is made of a nickel-cobalt-lithium selective adsorbent as described in claim 6, wherein the metal is any one of nickel and cobalt or a combination of nickel and cobalt.
8. A method for extracting lithium from sodium-containing brine, characterized in that, The extractant containing the nickel-cobalt-lithium selective adsorbent as described in claim 6 is used, and the initial aqueous phase pH is controlled to be 9-13.5, preferably 10-13.
5.
9. The method according to claim 8, characterized in that, Includes the following steps: S11: The above-mentioned nickel-cobalt-lithium selective adsorbent is contacted with a lithium-containing sodium solution for extraction, and then solid-liquid separation is performed to obtain lithium-loaded adsorbent and raffinate. S12: The lithium-loaded adsorbent is subjected to a second back-extraction using an acid solution, followed by solid-liquid separation to obtain the back-extracted adsorbent and lithium back-extraction solution.
10. The method according to claim 8 or 9, characterized in that, The nickel-cobalt-lithium selective adsorbent is first subjected to alkaline treatment before extraction. Preferably, the adsorbent transformation treatment uses 0.1-1M NaOH solution.
11. The method according to claim 9, characterized in that, The acid solution is selected from sulfuric acid solution and / or hydrochloric acid solution, wherein the concentration of the sulfuric acid solution is 0.5-6 mol / L and the concentration of the hydrochloric acid solution is 1-8 mol / L.
Citation Information
Patent Citations
Preparation method of D301 macroporous weekly acidic styrene type anion exchange resin
CN101781379B
